Penggunaan Bunyi Glotal dalam Tuturan Bahasa Madura oleh Mahasiswa Universitas Muhammadiyah Jember - Fadilah Rahmawati; Cantika Kunthi Prabandari; Tasya Madinah; Hasan Suaedi (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of glottal sounds is a unique feature of the Madurese language, serving as both a phonological marker and a linguistic identity. This study aims to analyze the patterns of glottal sound usage in the speech of students at Muhammadiyah University of Jember, focusing on formal and informal contexts. The research employs a descriptive qualitative approach, collecting data through observation, in-depth interviews, and analysis of speech recordings. Results reveal that glottal sounds are more frequently used in informal communication than in formal settings, reflecting the speakers' social and cultural dynamics. These findings provide important insights into how regional languages are preserved in academic environments and contribute to the efforts of preserving the Madurese language.